Overview of the trade of reptile taxa consumed for therapeutic purposes across Africa - Moshoeu, Thibedi Tshepo Jacob (My University, 2017)
Although zootherapy is complementary to the body of knowledge on plant-based medicine, few African studies have attempted to identify and record the trade of therapeutic reptiles. This report analyses and provides an overview of the continent-wide (African) trade of reptiles for therapeutic purposes. The results show that at least 101 reptile species are used for therapeutic purposes in traditional medicine markets across Africa. Among these 101 therapeutic species, 40 are listed on the IUCN Red List and 44 are included in some of the CITES Appendices. Additionally from a species rarity perspective, the most frequently recorded species tended to be very common where they occur, and the least frequently recorded species tended to be the rarest. When enumerating in terms of the African Union regions, West Africa (especially Togo) and southern Africa (especially South Africa) yields the highest number of species recorded. The most sought therapeutic species appear to be Crocodylus niloticus, which was recorded in 17 countries, followed by Varanus niloticus (n=9 countries) and Python sebae (n=8 countries). With records in 22 countries each, pythons and crocodiles (morphospecies) appear to be the most sought for therapeutic purposes. In light of the deficit in information on trade and/or utilisation, the results demonstrate the urgent need to understand and identify the species traded in the context of reptile conservation.
A research report submitted in partial fulfilment of the requirements for the degree of Masters (MSc. by Course work and Research Report) School of Animal, Plant and Environmental Sciences to the Faculty of Science at the University of the Witwatersrand, South Africa. September 2017.
Keywords: Animals--Therapeutic use; Wildlife conservation